The effect of users' grouping on the convergence behavior of the linear group-wise SIC - Bentrcia, A. (2004)
In this paper, we use the whitening filter theory to classify different linear group-wise successive interference cancellation multiuser detectors. Three major categories are distinguished namely the whitening filter, the partially whitening filter and the nonwhitening filter based group-wise successive interference cancellation detectors. Using the same theory, we study the effect of users' grouping on their convergence behavior. Our analyses are verified through simulation.